Um estudo sobre a formação inicial e continuada de professores de ciências : o ensino por investigação na construção do profissional reflexivo - Oliveira, André Luis de (2013)
The comprehension of basic concepts of Science and the conscience of the possible consequences such knowledge produces require the education of a qualified professional engaged with the educational process. The teacher needs to have the opportunity of conciliating theory and practice to perform a constant attendance to the work developed in the classroom, with methodologies appropriate to approximate the students, the area conceptual contents and aspects of everyday life. With such aim, we propose to investigate initial and continuing education of Science teachers participating in Programa Institucional de Bolsas de Iniciação à Docência - PIBID (Institutional Scholarship Program of Initiation to Teaching), of a Biological Sciences course in a State University in the State of Paraná, based on theoretical and methodological fundamentals of Science Teaching by research and education of reflexive teachers. Thereunto, the data were recorded by applying an initial questionnaire, discussions in the study group for the implementation of teaching by research, analysis of teaching plans and experience reports. The conceptions and practices on the Science teaching by research analyzed in this study allowed to infer that it is not possible to conceive an effective education dissociated of the subjects of learning social reality; neither it is possible to ignore the professionals responsible to guide the students into the comprehension of scientific concepts. In the context of this research, we can affirm that PIBID has been an important initiative for the education of reflexive teachers. In face of these assumptions, we suggest a new orientation in the process of teachers' education that, among other aspects, can integrate research and teaching, characterizing other profile for this professional in the acting field, that is a reflexive teacher.